The Neolithic Site of San Martino — Sicily: Working and Circulation of Obsidian from Lipari - Quero Tania; Martinelli Maria Clara; Giordano Letterio (Open Archaeology, 2019)
The settlement of San Martino was found in 2008 on the Northern coast of Sicily (near the city of Spadafora — Messina). It is located on a hill slope about 4 km from the coast of the Tyrrhenian Sea, near an ancient river which is no longer present today. The stratigraphy included two Neolithic levels: the oldest one belonged to the Stentinello culture (middle Neolithic — 6th-5th millennium BC cal) and the later one belonged to the Diana culture (Late Neolithic — 4th millennium BC cal). The San Martino lithic assemblage consists of a very significant amount of obsidian knapping products that have allowed us to examine the procurement, exploitation and circulation of this raw material, from the source on the island off the coast of Sicily, during the Neolithic period. Considering its strategic location and some analogies with other settlements nearby, the site of San Martino was probably part of the Lipari obsidian networks of exchange.